Significant Association Between Polymorphisms of Wnt Antagonist Genes and Lung Cancer - (:unkn) unknown (BMJ PUBLISHING GROUP, 2015)
Further elucidation of the molecular mechanisms underlying lung cancer (LC) is essential for the development of new effective therapeutic agents. Recently, involvement of Wnt antagonists in oncogenesis has been demonstrated in several cancers. The investigation of their contribution to lung carcinogenesis is still under investigation. We aimed to investigate whether there is a susceptibility or preventive effect of Wnt antagonist gene polymorphisms on the development and/or prognosis of LC. We investigated 110 LC patients and 160 controls. Single-nucleotide polymorphisms of Wnt antagonist genes including DKK2 (rs17037102), DKK3 (rs3206824), DKK3 intron4 G/C (rs7396187), DKK4 (rs2073664), and sFRP4 (rs1802074) were analyzed using nested polymerase chain reaction and restriction fragment length polymorphism. Results showed that patients with DKK3 AA compared with controls have a decreased risk of LC (adjusted for smoking habit, body mass index, and familial history) (P = 0.02; odds ratio [OR],0.08; 95% confidence interval [95% CI], 0.01-0.7). It was found that, for sFRP4 polymorphism, patients with GG and GA genotypes versus AA genotype controls showed a decreased risk for LC (P = 0.01; [OR, 0.19; 95% CI, 0.05-0.73 for GG genotype]; [OR = 0.18, 95% CI, 0.04-0.72 for GA genotype]). In addition, a decreased risk of LC was also found for the genotype combination of DKK3 (rs3206824) GG and sFRP4 AG + GG (P = 0.004; OR, 0.12; 95% CI, 0.02-0.58). We suggest that these 2 polymorphisms have a protective effect on LC in this study.
Keywords: DKK genes; lung cancer; polymorphism; sFRP4 gene; SINGLE-NUCLEOTIDE POLYMORPHISMS; PROMOTER-HYPERMETHYLATION; SMOKING; SFRP1; DKK3